Exploring the Learning Methods Used in Teaching English at SMP Kristen Makale - Nehru Pasoloran Pongsapan; Jones Cherady; Yizrel Nani Sallata; Andi Sadapotto (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this study is to find out what learning methods are most often used in teaching English at Makale Christian Junior High School. In carrying out this study, the researcher used descriptive qualitative research. Data analysis used qualitative data analysis, which is the process of reducing data, presenting data, and drawing conclusions. The purpose sampling strategy was used to obtain data from English teachers two who teach at Makale Christian Junior High School. The data were obtained using interview and observation. Based on the results of this study, the researcher concluded that there is one learning method that is most often used by teachers in teaching English at Makale Christian Junior High School, namely the lecture plus method or the lecture plus discussion and task (CPDT) method. and as for the reasons why teachers at Makale Christian Junior High School often use it in teaching because this method is very practical, efficient and also in the lecture plus method it includes almost all activities such as discussion, question and answer exercises and also practice. And as for the weaknesses and advantages of the lecture plus method, namely students can actively participate through questions and answers and exercises, it is very easy to use or practical and also very efficient and has almost included several teaching and learning activities such as questions and answers, discussions, exercises and assignments. while the weakness is that the learning process does not occur in two directions because the lecture plus method is more teacher-centered than with students. From the results of the data analysis above, the researcher concludes that some of the methods used by English teachers at Makale Christian Junior High School in learning English are very helpful for students so that they can achieve effective and efficient learning outcomes and optimize student learning achievement